2015
DOI: 10.4018/ijsem.2015010104
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Rural Tourism of Lower Danube Region in Serbia

Abstract: Sustainable tourism implies preserved space, prevents ecological and socio-cultural devastation, but at the same time encourages tourism development. Their application and adequate implementation increases the chance of a tourist destination that will be able to develop sustainable tourism, so the aim of this paper is to separate characteristics and principles of sustainability on certain areas and to show their advantages and limitations. In this paper are introspected factors of tourism development, both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Acording to Štetić, Pavlović, & Jovanović (2015), rural tourism has long been considered the means of accelerating economic and social development, and has become a development tool for many rural areas. The relationship between rural tourism and other tourism forms practiced in the rural areas is extremely important, because it establishes the coonections between natural, human, economical and social parameters, in order to insure all factors that lead to tourist growth and durable development (Nedelcu, 2014).…”
Section: Introduction and Context Of The Studymentioning
confidence: 99%
“…Acording to Štetić, Pavlović, & Jovanović (2015), rural tourism has long been considered the means of accelerating economic and social development, and has become a development tool for many rural areas. The relationship between rural tourism and other tourism forms practiced in the rural areas is extremely important, because it establishes the coonections between natural, human, economical and social parameters, in order to insure all factors that lead to tourist growth and durable development (Nedelcu, 2014).…”
Section: Introduction and Context Of The Studymentioning
confidence: 99%
“…Among numerous studies on sustainable tourism are those related to measuring sustainability and conceptual challenges (implementation of measurement, impact of different contexts on measurement, legal compliance)(Bell and Morse 1999;Butler 1998;Ko 2005;Castellani and Sala 2010). Taking into consideration the heterogeneity of the topic, some authors concluded that the universal program of the sustainable development of tourism does not exist because it depends on the characteristics of the area(Nedelcu 2010;Štetić et al 2015;Mazilu and Gheorgheci 2015).…”
mentioning
confidence: 99%